Lessons Learned From Presumptive Condition Lists in Veteran Compensation Systems - Hall, Amy L.; Demers, Paul A.; VanTil, Linda; MacLean, Mary Beth; Dalton, Maria E.; Batchelor, Trish; Rushton, Lesley; Driscoll, Tim R. (Frontiers in Public Health, 2022)
*Presumptive condition lists formally accept connections between military factors and veteran health conditions *An environmental scan of such lists and their evidentiary basis was conducted across four veterans’ administrations to inform other administrations considering the development of such lists *Information on included conditions, qualifying military factors, and scientific processes was obtained through targeted internet searches and correspondence with veterans’ administrations *The content of presumptive condition lists across jurisdictions varied by conditions included, as well as military eligibility requirements (e.g., service in particular conflict, context, or time period) *Scientific review processes to develop lists also varied across jurisdictions *Findings indicate that evidence and experience may be leveraged across compensation systems (veteran and civilian) *Ongoing research to understand links between military exposures and veteran health is recommended